Association of Beta-Thalassaemia and Hypogonadotropic Hypogonadism - Angela Vidal; Carolin Dhakal (Case Reports in Obstetrics and Gynecology)
Thalassaemic syndromes are among the most common haemoglobinopathies and are associated with high morbidity and mortality. Because of the various treatments, a secondary endocrinopathy due to iron overload—haemosiderosis—can occur, causing hypopituitarism leading to hypogonadotropic hypogonadism (HH) and infertility. We present a case of secondary amenorrhoea in a patient with beta-thalassaemia and a history of multiple therapies in her adolescence, such as multiple transfusions, chemotherapy, and allogeneic bone marrow transplantation, who presented with HH and premature ovarian insufficiency.